Assess the Knowledge Level Regarding Prevention of Cervical Cancer Among Bachelor of Science Students at Selected Nursing College in Bengaluru - Y. Preethi; S. Bhagyalakshmi; Hephzibah Keren (International Journal of Oncological Nursing and Practices, 2025)
Background: Cervical cancer is a major global health concern and one of the primary causes of cancer-related fatalities in women, with particularly high incidence rates in India. Early detection and prevention are crucial, but awareness remains insufficient, especially among future healthcare professionals like nursing students. This study evaluates the knowledge of first-year Bachelor of Science (BSc) nursing students regarding cervical cancer prevention. Materials and Methods: A non-experimental, descriptive research design was utilized for the study. A random sample of 60 first-year female BSc nursing students was selected. Data were gathered through a structured questionnaire, which covered demographic details and assessed knowledge regarding the fundamentals of cervical cancer, its risk factors, diagnostic methods, and prevention strategies. Descriptive and inferential statistical techniques, including Chi-square tests, were applied to analyze the data and examine relationships between knowledge levels and demographic factors. Results: The demographic data indicated that the majority of students were aged 18–19 years (60%), predominantly Hindus (60%), unmarried (100%), and without children (100%). While 25% reported a family history of cancer and 41.7% had some previous knowledge about cervical cancer, only 6.7% were vaccinated against it. The knowledge levels revealed that 61.7% of students had an average understanding of cervical cancer prevention, 36.7% had above-average knowledge, and 1.6% had below-average knowledge. Chi-square analysis showed that most demographic factors did not significantly affect knowledge levels, except for family history of cancer, which was significantly associated with better knowledge. Conclusion: The study highlights that first-year BSc nursing students generally have an average understanding of cervical cancer prevention. Although family history of cancer appears to enhance knowledge, factors such as age, religion, and prior knowledge do not significantly impact their understanding. These results highlight the importance of focused educational initiatives that stress the prevention of cervical cancer and the significance of vaccination. Improving educational efforts will better equip nursing students to promote cervical cancer awareness and preventive practices in their future careers.
Keywords: Preventive measures; cervical cancer; educational programs; knowledge assessment; nursing students